OsCKq1 Regulates Heading Date and Grain Weight in Rice in Response to Day Length - Eun-Gyeong Kim; Yoon-Hee Jang; Jae-Ryoung Park; Xiao-Han Wang; Rahmatullah Jan; Muhammad Farooq; Sajjad Asaf; Saleem Asif; Kyung-Min Kim (Rice, 2024)
Abstract Background Photoperiod sensitivity is among the most important agronomic traits of rice, as it determines local and seasonal adaptability and plays pivotal roles in determining yield and other key agronomic characteristics. By controlling the photoperiod, early-maturing rice can be cultivated to shorten the breeding cycle, thereby reducing the risk of yield losses due to unpredictable climate change. Furthermore, early-maturing and high-yielding rice needs to be developed to ensure food security for a rapidly growing population. Early-maturing and high-yielding rice should be developed to fulfill these requirements. OsCKq1 encodes the casein kinase1 protein in rice. OsCKq1 is a gene that is activated by photophosphorylation when Ghd7, which suppresses flowering under long-day conditions, is activated. Results This study investigates how OsCKq1 affects heading in rice. OsCKq1-GE rice was analyzed the function of OsCKq1 was investigated by comparing the expression levels of genes related to flowering regulation. The heading date of OsCKq1-GE lines was earlier (by about 3 to 5 days) than that of Ilmi (a rice cultivar, Oryza sativa spp. japonica), and the grain length, grain width, 1,000-grain weight, and yield increased compared to Ilmi. Furthermore, the culm and panicle lengths of OsCKq1-GE lines were either equal to or longer than those of Ilmi. Conclusions Our research demonstrates that OsCKq1 plays a pivotal role in regulating rice yield and photoperiod sensitivity. Specifically, under long-day conditions, OsCKq1-GE rice exhibited reduced OsCKq1 mRNA levels alongside increased mRNA levels of Hd3a, Ehd1, and RFT1, genes known for promoting flowering, leading to earlier heading compared to Ilmi. Moreover, we observed an increase in seed size. These findings underscore OsCKq1 as a promising target for developing early-maturing and high-yielding rice cultivars, highlighting the potential of CRISPR/Cas9 technology in enhancing crop traits.